Narcissism and Advertising: Youth Centre Marketing - Francis Gnana Sekar, I. (Indian Journal of Marketing, 2005)
In recent years a great deal of concentration and attention has focused on global marketing. The Tri-national Companies apply a common marketing strategy for all countries for their effective sales promotion. Global marketing paves the way for global advertising. The concept of advertising helps the marketer to remove the hindrance of knowledge. At the same time advertising is a brutal business where mistakes can be a very costly affair. As a consequence, this will affect the socio,economic and cultural background of the country. There is a debate, over standardization versus localization of marketing and advertising strategies Professor Theodore Heritt (1983) who observes the worldwide market place has become homogenized and consumer's basic needs, wants, and expectations transcend geographic, national, and cultural boundaries.